Optical phase‐locking of two longitudinal modes of a dual‐mode laser for millimetre‐wave signal generation. Issue 9 (4th April 2016) - Hyodo, M.; Sato, K.; Kawakami, A.; Saito, S.; Watanabe, M.; Adachi, M.
Abstract : Phase‐locking of two longitudinal oscillating modes of a dual‐mode microchip laser that has 101 GHz longitudinal‐mode spacing has been successfully demonstrated by using electronic negative‐feedback control. Since the two longitudinal modes were oscillating simultaneously in the same laser cavity, the common‐mode fluctuation cancels, resulted in the small required control bandwidth of ∼4 kHz. This narrow‐bandwidth phase‐locking technique is useful for generating high‐spectral‐purity millimetre‐wave signals with a considerably simpler setup.